Household Savings in Transition Economies - Denizer, Cevdet; Wolf, Holger C.; Ying, Yvonne (World Bank, Washington, DC, 2015)
During the transition from central planning to market economies now under way in Eastern Europe, output levels first collapsed by 40 to 50 percent in most countries, then staged a modest recovery in the last two years. Longer-term revival of growth requires a resumption of investment and thus, realistically, of domestic savings. To explore the determinants of household savings rates in transition economies, the authors studies matching household surveys for three Central European economies: Bulgaria, Hungary, and Poland. They find that savings rates strongly increase with relative income, suggesting that increasing income inequality may play a role in determining savings rates. Savings rates are significantly higher for households that do not own their homes or that own few of the standard consumer durables - possibly because, with no retail credit or mortgage markets, households must save to purchase houses and durables. The influence of demographic factors broadly matches earlier findings for developing countries. Perhaps surprisingly, variables associated with the households position in the transition process - including either sector of employment (public or private) or form of employment - do not play a significant role in determining savings rates.